Analysis the Performance of Nursing Based on Work Culture in the Hospital of Nahdlatul Ulama Jombang - Ningrum, Selfya; Koesnadi; Suhita, Byba Melda (Journal for Research in Public Health, 2020)
Not all nurses are able to carry out its performance well. There are several factors that influence nurse can't perform the appropriate standards set forth among them, the number of non nursing tasks that must be done, the limited amount of power nurse nurses and others. The importance of maintaining and improving the performance of a nurse in a Hospital, given the performance of the nurses is important as the wheel prime mover and spearhead of a hospital. Good bad judgment about the hospital will certainly be judged from his nurse performance especially when providing service to the community. The goal of research to analyze the performance of Nursing based on work culture in the Hospital of Nahdlatul Ulama Jombang. Design of the research are analytical quantitative with crossectional approach. The variable are research were organizational climate, work ethic, discipline working as independent variables. The dependent variable as a performance. This research population are of all the nurses who served in the inpatient room at Hospitals of Nahdlatul Ulama Jombang amounted to 140 people. Samples taken with the technique of cluster random sampling as much as 103 respondents. Data is collected with instruments ceklist and processed in coding, editing, tabulating and scoring as well as tested with linear regression test. Linear regression results indicate that partially and simultaneously the value of p values < 0,05 so that there were influence on the climatic Organization, work ethic and discipline of work and the simultaneous influence of 88.6%. Employee performance can be affected by several factors including the climate of the Organization, work ethic and discipline work. An employee who has a high work ethic describes a high morale, and have a high work discipline will tend to have better performance